An illustrated key to fruit flies (Diptera: Tephritidae) from Peninsular India and the Andaman and Nicobar Islands - David, K. J.; Ramani, S. (Zootaxa, 2011)
An illustrated key and a checklist are provided for 126 species of fruit flies under 46 genera in four subfamilies namely Dacinae, Phytalmiinae, Tephritinae and Trypetinae. Among these, Acroceratitis striata (Froggatt), Rhochmopterum venustum (de Meijere) and Themara yunnana Zia are new records for India. Bactrocera yercaudiae Drew is placed as a synonymn of Bactrocera digressa Radhakrishnan.